(untitled) (GYMNASIUM, 2008)
The purpose of this paper is an N-of-1 study, as are named the studies on a single case. Such studies are considered to be “modest” and their purpose is not to discover the “secrets of nature” and sometimes not even to collect data which could help future patients. The intention is to gather as many data/alternatives as possible which will help the establishing of optimum therapeutic conduct, the best for the patient in discussion. The case of a paraplegic patient encountered in the educational process, student at the Socio-Human Sciences Faculty, University of Oradea, 30 years old, has determined us to start this study, approaching a, not at all simple, interdisciplinary issue. For many such persons, a life close to normal is yet possible. Rehabilitation through physical therapy and occupational therapy has the purpose to help the patient reach her highest level of independence under the given circumstances, using to the maximum what she can.